Communications technology guidelines for EMS - Marihart, D.J.
The purpose of this Guideline Technical Paper is to provide a summary of the different communications technologies available for use or application with EMS/SCADA system projects. All of the various communication media are addressed with a brief description along with tables of the advantages and disadvantages of each and recommendations for choosing the most appropriate communication technology. The technologies discussed are: twisted pair metallic cable; coaxial metallic cable; fiber optic cable (either optical power ground wire (OPGW), all dielectric self supporting (ADSS), or wrapped types (WOC)); distribution line carrier (DLC); power line carrier (PLC); satellite (VSAT, LEO, others); leased service; VHF radio (mobile); point-to-point UHF radio; multiple address radio system (MARS) 400/900 MHz UHF radio; trunked mobile UHF radio; spread spectrum UHF radio (monitor frequency for potential interference before installation); and microwave radio (2-40 GHz)
Keywords: 2 to 4 GHz; 400 MHz; 900 MHz; EMS/SCADA systems; OPGW; UHF radio; VHF mobile radio; VSAT; All dielectric self supporting optical cable; Coaxial metallic cable; Communications technology guidelines; Distribution line carrier; Fiber optic cable; Leased service; Microwave radio; Monitor frequency; Multiple address radio system; Optical power ground wire; Point-to-point UHF radio; Potential interference; Power line carrier; Satellite communication; Spread spectrum UHF radio; Trunked mobile UHF radio; Twisted pair metallic cable; Wrapped